Eliminasi Waste pada Proses Produksi Melalui Penerapan Lean Manufacturing dengan Metode VSM, WAM, Dan VALSAT(Studi Kasus PT RST) - Andika Rangga Aditya Perdana Putra; Muhammad Hengki Riawan Putra; Kusno Hadidjija (Fakultas Teknik Universitas Tulang Bawang, 2026)
This study focuses on improving the production efficiency of air nipples at PT RST through Lean Manufacturing by reducing process times that exceed takt time and minimizing waste, particularly defects, which increased from 1.8% (February 2024) to 2.4% (September 2024). The study implements three Lean tools, namely VSM, WAM, and VALSAT. The results show that three production processes—Cutting (42.32 seconds > 39.60 seconds), Turning 1 (97.08 seconds > 91.80 seconds), and Turning 2 (46.80 seconds > 34.20 seconds)—have cycle times exceeding takt time. Additionally, four types of waste were found to have the greatest impact on production efficiency: motion (19.74%), defect (18.47%), inventory (17.61%), and overproduction (17.06%). The main causes of waste include operators’ dependence on team leaders, limited work facilities, and the absence of a pull system. Strategic recommendations include the implementation of TPM, JIT, and the addition of work facilities. These improvements are estimated to reduce production lead time from 557.14 seconds to 453.72 seconds, a decrease of 18.56%. Keywords: Lean Manufacturing, Value Stream Analysis Tools, Value Stream Mapping, Waste, Waste Assessment Model